Design and Simulation of Silicon-Based Suspension Beams for Various MEMS Sensors. (6th May 2022) - Taj, Mohammad; Pitchaiah, Telagathoti; Sasikumar, Bashyam
Abstract : This paper mainly concentrates on finding maximum displacement and Eigen frequency for microelectromechanical system (MEMS) inertial sensors with various beam structures. In this work, six different shapes of beams are attached with one set of electrodes to find which structure exhibits the maximum displacement with less cross-axis displacement and to observe the operating frequency. The momentum of the beams is directly proportional to the thickness and length, which provides the maximum flexibility to produce momentum on proof mass. The beam thickness is 5 um for all proposed sensors and the momentum has been observed by changing different shapes of beam structures. The momentum occurred on proof mass due to applied physical energy. The same amount of physical energy is applied to all structure and the momentum, quality factor, and displacement are measured which had been compared and the table is given.